The Issue of Unveiling the Aurah for Women in Quran. A Critical and Contextual Analysis of Surah al-Nūr [24]: 58-61) - Moh. Nailul Muna (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This paper aims to contruct the permissible rules that allow woman to unveil her Aurah based on (QS. Al-Nūr [24]: 60). The study of aurah has reaped many polemics from time to time, this is based on the fact that the Qur'an does not provide explicit information about the extent to which the aurah must be covered. In response to this, the scholars can be divided into two groups, the first is those who are strict in setting the limits of aurah on the historical manner. Meanwhile, in the other group, figures such as Syahrur gives freedom within deciding the limits of woman’s aurah according to the minimum and maximum limits. One of the reasons held by the second group in covering aurah term is that it could cause the difficulty or masyaqqah. In response to that, this paper contributes to bridge the gap based on (24: 60) which contains the permissibility for qawāid minan nisā’ to reveal his outer clothing. Through the linguistic approach which is relation of text belongs to Salwa MS El-Awa. The application of this method considers the aspects of coherence and relevance in the text. Coherence is intertwined with the component of the text whereas the relevance covers the wider aspect that could not be clearly seen by the text in which related to munasabah analysis. Then, this task approaches the problem through phenomenology view. The result appeared that religion actually allows an old or young woman who has not charm or attraction to open her khimār, niqāb and ridā’ on condition that has experienced menopause, has lost his lust, and does not intend to show jewelry, and she is in a private sphere; home